2015
DOI: 10.1007/s00018-015-1887-1
|View full text |Cite
|
Sign up to set email alerts
|

The novel role of miRNAs for tamoxifen resistance in human breast cancer

Abstract: Public reporting burden for this collection of information is estimated to average 1 tiour per response, including ttie lime for reviewing instmctions, searctiing existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of infomnation, including suggestions for reducing this burden to Washington Headquarters Services, Directorate for Information Operations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 81 publications
1
20
0
Order By: Relevance
“…In addition, recent studies in ERα-positive cell lines have shown that restoring certain miRNAs sensitized these cells to TAM. Such miRNAs include miR-342 [201], miR-375 [202], miR-451 [203], miR-261, miR-575 [204], miR-200b and miR-200c [205,206] (Figure 8). …”
Section: Tam Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, recent studies in ERα-positive cell lines have shown that restoring certain miRNAs sensitized these cells to TAM. Such miRNAs include miR-342 [201], miR-375 [202], miR-451 [203], miR-261, miR-575 [204], miR-200b and miR-200c [205,206] (Figure 8). …”
Section: Tam Resistancementioning
confidence: 99%
“…Recent studies have focused on drugs targeting nucleic acids in order to develop breast cancer therapies, with the objectives centering on either inactivating ncRNAs, which confer resistance to TAM, or enhancing the effect of ncRNAs that restore susceptibility to anti-estrogen treatment [206,234,235]. These emerging therapies include ribozymes, siRNAs, antisense oligonucleotides (ASOs) or their chemically tailored analogs (known as locked nucleic acids, LNAs), which can alter RNA splicing and induce degradation of the targeted RNA via RNaseH.…”
Section: Clinical Use Of Tam In Combination With Other Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its significance over cell proliferation has also been reported in ER À breast cancer cells indicating its ER independent effect [4]. Eventhough, Tamoxifen has been approved to be the gold standard for Breast cancer therapy the major problem encountered with Tamoxifen is resistance after long term treatment [5,6].…”
Section: Introductionmentioning
confidence: 98%
“…Approximately 70% of human breast cancers present as ER‐positive, a cancer cell subtype that requires estrogen for survival and growth. Endocrine therapy including tamoxifen, fulvestrant and letrozole is currently recognized as the most effective and clearly targeted form of adjuvant therapy for hormone‐sensitive breast cancer . However, the prevalence of primary and acquired resistance severely restricts the efficacy of these agents in the clinic, and the development of new treatments for breast cancer is a research priority.…”
Section: Introductionmentioning
confidence: 99%